A utility value intervention to support student engagement in online upper-level undergraduate courses - Shillington, Katie J.; Lo, Stanley M.; Hobbie, Lawrence (Frontiers in Education, 2025)
IntroductionUtility value interventions are assignments designed to increase student motivation by helping them find personal value in what they are learning. Previous studies have found utility value interventions to lead to improved student outcomes. The purpose of this study was to investigate the impact of a utility value (UV) intervention on the academic outcomes of undergraduate students in online courses, compared to students in a control condition.MethodsA total of 1,243 students in upper-level online biology courses participated and were randomized either to UV (n = 589) or control (n = 654) conditions.ResultsThe intervention had a positive effect, as UV participants engaged with and participated in their courses significantly more than students in the control condition. Utility value participants also wrote significantly longer essays, and used more pronouns, social process words, and cognitive process words than students in the control condition. However, UV participants did not have higher course grades than students in the control condition. Additionally, underrepresented minority (URM) status was a significant predictor of course grade; non-URM students had significantly higher course grades than URM students.DiscussionThe utility value intervention did have a positive effect on student course engagement but, contrary to most previous studies, did not lead to higher student course grades, perhaps because these classes were online, because they were upper-level instead of introductory, or because the study was conducted during the COVID-affected spring 2020 quarter. Findings from this study can help institutions decide whether to adopt UV interventions in online courses.